Diurnal pattern of salivary cortisol and progression of aortic stiffness: Longitudinal study - Ikeda, Ai; Steptoe, Andrew; Shipley, Martin; Abell, Jessica; Kumari, Meena; Tanigawa, Takeshi; Iso, Hiroyasu; Wilkinson, Ian B.; McEniery, Carmel M.; Singh-Manoux, Archana; Kivimaki, Mika; Brunner, Eric J. (Psychoneuroendocrinology, 2021)
The positive direct relation between stress and the development of cardiovascular disease has increasingly been recognized. However, the link between hypothalamic-pituitary-adrenal (HPA) dysregulation and subclinical cardiovascular disease has not been studied longitudinally. We investigated the relation of diurnal salivary cortisol, as a biological marker of stress levels, with progression of aortic stiffness over five years. A total of 3281 people (mean age 65.5) in the Whitehall II prospective study provided six saliva samples on a single weekday. We assessed the diurnal salivary cortisol using the daytime slope and bedtime level. Aortic stiffness was measured by carotid-femoral pulse wave velocity (PWV) at baseline (2007–2009) and five years later (2012–2013). Linear mixed models were used to estimate the association of diurnal salivary cortisol with baseline PWV and five-year longitudinal changes. Diurnal salivary cortisol were not associated with PWV at baseline. Among women but not men, a 1-SD shallower salivary cortisol slope at baseline was associated with a five-year increase in PWV (β = 0.199; 95% CI = 0.040, 0.358 m/s) and higher bedtime cortisol level (β = 0.208, 95% CI = 0.062, 0.354 m/s). Dysregulation of the HPA axis measured using salivary cortisol (shallower slope, higher bedtime level) predicted the rate of progression of aortic stiffness among women. •The first longitudinal study was conducted to examine the relation of HPA dysregulation with aortic stiffness.•This study gives some insight into stress-related biological alterations linked to cardiovascular disease development.•Our findings demonstrated that the effects of HPA dysregulation on the progression of aortic stiffness may be sex-specific.